Eastern Europe: Cultural Construct or Way(s) of Living? - Bursztyka, Przemysław (Eidos. A Journal for Philosophy of Culture, 2025)
Preview: The category of Eastern Europe is deeply problematic. It is so on many levels. To better realize that, it suffices to ask a citizen of any country once belonging to the “Eastern bloc” if they consider themselves Eastern European. In most cases they will do whatever possible to slip away from such a categorization, considering it deeply shameful. “Eastern Europe” sounds like a curse, a stain, a stigma. Obviously, on a superficial level there are some clear political, social, and economic reasons for that; reasons associated mostly with the postwar period when almost half of the continent found itself in the sphere of influence of the Soviet Union. Being on the wrong side of the Iron Curtain meant, for several generations, a painful condition of debasement, deprivation of the basic human rights, economic poverty, destruction of the social sphere, lack of possibilities, and so forth. So, the category in question sounds like a reminder of this painful past. However, it goes back far beyond Sovietism. For all the countries located on the eastern frontiers of Europe it is very clear: the main motivation for escaping such a categorization lies in the fact that Eastern Europe has, for a very long time, been commonly recognized as the sphere of Russia’a cultural dominion. It suffices to look at the departments of Eastern European/Slavonic studies among Western (e.g., Western European, US, Canadian) universities. In most cases, their names and programs a priori grant Russia and its culture a superior position. Thus, it is not surprising that being classified as “Eastern European” is seen and experienced as being associated with and/or subordinated to this monstrous cultural formation. This is an erroneous way of viewing Eastern Europe, if only because Russia itself simply does not belong to Europe. And in fact, it never has. It has never genuinely shared the cultural patterns characteristic of the European cultural project, its guiding values, and ideals.